Edwards, Germany, and transatlantic contexts - Bezzant, Rhys S. (New directions in Jonathan Edwards studies, 2022)
Angaben zur beteiligten Person Bezzant: Rev'd Canon Dr Rhys Bezzant has tenure as Senior Lecturer in the field of Christianity in History at Ridley College, in Melbourne, Australia and is a priest in the Diocese of Melbourne.
Online veröffentlicht: Dezember 2021
Keywords: Edwards, Jonathan -- 1703-1758; Europe -- Church history; United States -- Church history; Aufsatzsammlung; Erweckungsbewegung; Protestantismus; Deutschland; Rezeption; Edwards, Jonathan; Geschichte; Philosophie; Frömmigkeit